MOF confinement precious metal composite material and preparation method and application thereof

By limit-domain precious metal nanoparticles in MOF catalysts, the problems of insufficient MOF activation oxygen capacity and complex loading of precious metals are solved, and efficient removal of formaldehyde and improved catalyst stability are achieved.

CN119425802AActive Publication Date: 2025-02-14INST OF EARTH ENVIRONMENT CHINESE ACAD OF SCI
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510025691.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-14
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing MOF catalyst has low oxygen activation capacity and cannot achieve complete removal of formaldehyde. At the same time, the preparation technology of MOF-supported precious metals is complex.

Method used

By dispersing zirconium salt or hafnium salt in a mixed solvent of N,N-dimethylformamide and ethanol, combining noble metal precursors, MOF domain precious metal composite materials are prepared by a one-step oil bath method, using monomer organic acids and 2- Competing coordination effect of aminoterephthalic acid constructs defective MOF and in situ confined precious metal nanoparticles.

Benefits of technology

The activation oxygen capacity of the MOF catalyst is improved, the efficient adsorption and catalytic conversion of formaldehyde is achieved, the precious metal loading process is simplified, and the stability and activity of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425802A_ABST
    Figure CN119425802A_ABST
Patent Text Reader

Abstract

The invention discloses an MOF confinement precious metal composite material and a preparation method and application thereof.The preparation method comprises the steps that zircon salt and / or hafnium salt are / is dispersed in a mixed solvent of N, N-dimethylformamide and ethyl alcohol, and a metal salt solution is prepared; dispersing precious metal precursor powder in ethanol to prepare a precious metal precursor solution; and then uniformly mixing the metal salt solution with a noble metal solution, adding monobasic organic acid and 2-aminoterephthalic acid, and stirring for reaction to prepare the MOF confinement noble metal material. The catalyst is mild in preparation reaction condition, simple in process and high in yield, is suitable for efficiently catalyzing and purifying formaldehyde pollutants in air at normal temperature, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of MOF nanocatalyst development, and relates to a MOF confined noble metal composite material and a preparation method and application thereof. Background Art

[0002] Formaldehyde in the air is one of the typical toxic gaseous pollutants. It is widely derived from primary emissions from home building materials, decorative materials, daily necessities, and secondary reactions of volatile organic compounds produced by combustion activities such as cooking and smoking with strong oxidants such as ozone. The release cycle is as long as three to five years, and it has the risk of causing diseases such as nasopharyngeal cancer and leukemia. Severe formaldehyde pollution has become an important public environmental health issue, accelerating the urgent need for powerful formaldehyde removers.

[0003] Room temperature catalytic formaldehyde removal agents can activate O2 in the air in situ, spontaneously generate active oxygen to catalytically convert formaldehyde into CO2, and are suitable for formaldehyde treatment in indoor dim or unlit environments. Metal organic frameworks (MOFs) are porous compounds composed of metal ions / ion clusters coordinated with organic ligands. They have large specific surface area, flexible structure, and adjustable metal valence states, and have become a class of potential formaldehyde removal catalysts. However, most single MOFs currently have poor charge transfer ability caused by changes in the valence state of their own metal ions, resulting in low oxygen activation ability. They can only show good formaldehyde removal performance in static tests ("Synergetic Molecular Oxygen Activation and Catalytic Oxidation ofFormaldehyde over Defective MIL-88B(Fe) Nanorods at Room Temperature", Shuping Zhang, Yifan Zhuo, Chizoba I. Ezugwu, Chong-chen Wang, Chuanhao Li, Shengwei Liu, Environ. Sci. Technol., Vol. 55, No. 12, pp. 8341-8350, June 2021), or as formaldehyde adsorbents (patent CN201711091658.8), and cannot achieve complete formaldehyde removal. MOF can be used as a carrier to load precious metals, providing more oxygen-activated metal sites and promoting catalytic oxidation of formaldehyde. In addition, the current preparation technology of MOF loaded with precious metals is complicated, and usually requires a complex two-step method, that is, after the MOF material is prepared, sodium borohydride or hydrogen reduction method is used to load the precious metal ("Synergetic modulation of molecular oxygen activation and surface acidity / basicity on defective M / UiO-66m (M=Pt, Pd) for advanced oxidation of gaseousformaldehyde at room temperature", Yifan Zhuo, Xiuling Guo, Wei Cai, Tao Shao, Dehua Xia, Chuanhao Li, Shengwei Liu, Appl. Catal. B-Environ Energy., Vol. 333, No. 15, pp. 122789~122801, September 2023; Patent CN201911370310.1). Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a MOF confined precious metal composite material and a preparation method and application thereof, thereby solving the technical problem that the MOF in the prior art has low oxygen activation ability and cannot completely remove formaldehyde, and at the same time solves the technical problem that the preparation technology of MOF loaded with precious metals in the prior art is complicated.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a MOF confined noble metal composite material comprises the following steps: S1: Dispersing zirconium salt and / or hafnium salt in a mixed solvent of N,N-dimethylformamide and ethanol to obtain a metal salt solution; the ratio of the zirconium salt and / or hafnium salt to the mixed solvent of N,N-dimethylformamide and ethanol is (0.5-1.6) g:50 mL; dispersing a noble metal precursor powder in ethanol to obtain a noble metal precursor solution; S2: The metal salt solution and the noble metal solution are mixed evenly, wherein the mass ratio of the metal salt to the noble metal precursor is (0.5~1.6) g:(3~12) mg, and then a monobasic organic acid and 2-aminoterephthalic acid are added, and after stirring the reaction, the MOF confined noble metal material is obtained.

[0006] Preferably, in the mixed solvent of N,N-dimethylformamide and ethanol, the volume ratio of N,N-dimethylformamide to ethanol is 1:(5~1); the zirconium salt is any one of zirconium tetrachloride, zirconium nitrate and zirconium oxynitrate; the hafnium salt is hafnium tetrachloride or hafnium oxynitrate; and the concentration of the metal salt solution is 0.04~0.1 mol / L.

[0007] Preferably, the noble metal precursor is any one of chloroplatinic acid, chloroiridic acid and sodium chloropalladate; and the concentration of the noble metal precursor solution is 0.12-0.48 mg / mL.

[0008] Preferably, when the zirconium salt and the hafnium salt are dispersed in a mixed solvent of N,N-dimethylformamide and ethanol, the molar ratio of the zirconium salt to the hafnium salt is (0.8-0.2):(0.2-0.8).

[0009] Preferably, the monobasic organic acid is any one of formic acid, glacial acetic acid and propionic acid, and the volume ratio of the monobasic organic acid to the mixed solvent of N,N-dimethylformamide and ethanol in step S1 is (3-8):(20-50); the concentration of the 2-aminoterephthalic acid is the same as the molar concentration of the metal salt solution.

[0010] Preferably, in step S2, the stirring reaction is carried out at a temperature of 120-140° C. and for a time of 5-12 h.

[0011] Preferably, in step S2, after the stirring reaction, the product is centrifugally washed and dried at 100-160° C. for 12-20 hours to obtain the MOF confined precious metal material.

[0012] A MOF confined noble metal composite material is prepared by the above method; the particle size of the noble metal in the composite material is 2-3 nm.

[0013] The above-mentioned MOF confined precious metal composite material is used in the field of formaldehyde purification.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a MOF confined noble metal composite material. The method selects zirconium salt or hafnium salt (or a mixture of the two) and disperses it in a mixed solvent consisting of N,N-dimethylformamide (DMF) and ethanol, wherein DMF is used as a solvent to dissolve the zirconium salt or hafnium salt on the one hand, and can act as a noble metal reducing agent on the other hand, and ethanol reduces the overall viscosity of the solvent and increases volatility, thereby saving costs. This solvent combination is conducive to the uniform dispersion of the metal salt, providing a good foundation for subsequent reactions, and the noble metal precursor powder is dispersed in ethanol to form a uniform solution. This The first step is to ensure that the precious metal can be evenly distributed in the MOF structure; then the metal salt solution is mixed with the precious metal precursor solution, followed by the addition of a monobasic organic acid as a regulator and 2-aminoterephthalic acid as a ligand. The introduction of the monobasic organic acid not only helps to adjust the reaction environment so that the pH value is between 3 and 5, but also produces a competitive coordination effect with 2-aminoterephthalic acid, thereby introducing defects in the MOF structure. Because the monobasic organic acid contains one carboxyl group, and 2-aminoterephthalic acid contains two carboxyl groups, defects can be formed during the coordination process to improve the catalytic performance. This method uses DMF to replace the Pt of chloroplatinic acid in situ. 4+ With Cl - The six-coordinated configuration forms Pt(CO)2Cl2, Pt 2+ It can coordinate with -NH2 of 2-aminoterephthalic acid and be atomized. 0It is further reduced by DMF and aggregated into nanoparticles, thus avoiding the subsequent secondary reduction process, and the preparation process is simple. In addition, defects are introduced into the MOF structure through the competitive coordination between organic acid and ligand, which can confine metal sites and improve the performance of the catalyst. In addition, while MOF is formed, the in-situ generation and confinement of noble metal nanoparticles are achieved, avoiding the subsequent complex loading process and improving the stability and activity of the catalyst. And by utilizing the high specific surface area and pore structure of MOF, combined with the catalytic activity of noble metals, efficient adsorption and catalytic conversion of formaldehyde are achieved. At the same time, MOF is used to achieve in-situ confinement of the in-situ reduced noble metals, avoiding the agglomeration of noble metals in the conventional reduction process, which affects the catalytic performance of the noble metals. The method is simple in process and reasonable in design. MOF is used to achieve in-situ confinement of noble metals, avoiding the agglomeration of noble metals in the conventional reduction process, and effectively improving the adsorption and catalytic performance of the material for formaldehyde.

[0015] Further, another inventive point of the present invention is to disperse zirconium salt and / or hafnium salt in a mixed solvent of N,N-dimethylformamide and ethanol, wherein the volume ratio of DMF to ethanol is 1:(5-1); the concentration of the metal salt solution is 0.04-0.1 mol / L, DMF is a strong polar solvent, which has good solubility for many inorganic salts and organic substances, while ethanol is a relatively mild solvent, and its addition can reduce the toxicity of the entire solvent system and increase the volatility of the solvent, which is beneficial to subsequent treatment. The mixed use of the two can combine the advantages of the two, which not only ensures the full dissolution of the solute, but also improves the properties of the solvent. The volume ratio is 1:(5-1), and the design of this ratio range makes the solvent system neither too viscous (too high a proportion of DMF leads to increased solution viscosity, which is not conducive to the diffusion and mixing of the reactants), nor too dilute (too high a proportion of ethanol may reduce the solubility of the solute), and the appropriate ratio helps to form a uniform solution and promote the reaction. The concentration of the metal salt solution is 0.04~0.1mol / L. Too low a concentration will result in a slow reaction rate, affecting production efficiency, while too high a concentration will increase the viscosity of the solution and even cause solute precipitation, which is not conducive to the uniform reaction. The appropriate concentration range can ensure that the reaction proceeds at a faster rate while ensuring the quality and purity of the product. The mixed solvent of DMF and ethanol and the appropriate concentration setting help to evenly disperse the metal salt and the precious metal precursor, thereby increasing the contact opportunity between the reactants and accelerating the reaction process. The uniform solution system helps to form uniform MOF crystals and precious metal nanoparticles, avoiding product quality differences caused by uneven distribution of reactants.

[0016] Furthermore, another inventive point of the present invention is that the concentration of the noble metal precursor solution is 0.12~0.48mg / mL. By accurately adjusting the concentration of the noble metal precursor solution, the precise control of the noble metal loading in the MOF material can be achieved, which is crucial for optimizing the performance of the catalyst, because the loading of the noble metal directly affects its catalytic activity and selectivity. Within the appropriate concentration range, the noble metal precursor can be more effectively dispersed in the solvent, so that it can be more evenly embedded in the MOF structure during the subsequent reaction process, which avoids the agglomeration of the noble metal and improves the utilization rate of the noble metal. The catalytic performance of the noble metal is closely related to its particle size, dispersion and interaction with the carrier. By controlling the concentration of the noble metal precursor solution, the particle size and dispersion of the noble metal nanoparticles can be indirectly regulated, thereby optimizing the catalytic performance of the catalyst. Smaller particle size and uniform dispersion usually mean higher catalytic activity and better stability. Within the appropriate concentration range, the noble metal precursor solution can be more easily mixed with the metal salt solution, simplifying the preparation process. In addition, due to the moderate concentration, precipitation or stratification is not likely to occur during the reaction, which is conducive to the formation of uniform MOF confined precious metal materials.

[0017] Furthermore, another inventive point of the present invention is that when zirconium salt and hafnium salt are dispersed in a mixed solvent of N,N-dimethylformamide and ethanol, the molar ratio of the zirconium salt and the hafnium salt is (0.8~0.2):(0.2~0.8), and zirconium and hafnium, as metal centers, play different roles in the MOF structure. By adjusting the molar ratio of the two, the pore size, specific surface area, stability, and catalytic activity of the MOF material can be regulated, and this regulation helps to optimize the catalytic effect of the catalyst on formaldehyde purification. Zirconium and hafnium produce a synergistic effect in the catalytic process, that is, the catalytic effect is better than that of a single metal when the two act together. By adjusting the molar ratio, the best synergistic effect point can be found, so that the performance of the catalyst is further improved. At the same time, the addition of hafnium can improve the thermal stability and chemical stability of the MOF material. Therefore, by adjusting the molar ratio of zirconium and hafnium, the stability and service life of the catalyst can be improved while maintaining the catalytic activity. When the noble metal precursor solution is mixed with the metal salt solution, the different ratios of zirconium and hafnium will affect the distribution and particle size of the noble metal nanoparticles in the MOF structure. By optimizing the molar ratio, the uniform distribution and particle size control of the noble metal nanoparticles can be achieved, thereby improving the catalytic activity and selectivity of the catalyst.

[0018] Furthermore, another inventive point of the present invention is that the zirconium salt is any one of zirconium tetrachloride, zirconium nitrate and zirconium oxynitrate; the hafnium salt is hafnium tetrachloride or hafnium oxynitrate; the noble metal precursor is any one of chloroplatinic acid, chloroiridic acid and sodium chloropalladate, and these selected salts and precursors are common and easily available chemicals on the market, which helps to reduce the difficulty and cost of purchasing raw materials, and is also conducive to the industrial production of catalysts. These salts and precursors have good solubility in a mixed solvent of N,N-dimethylformamide (DMF) and ethanol and can form a uniform solution. In addition, they also have high reactivity and can react with ligands (such as 2-aminoterephthalic acid) under appropriate conditions to form a stable MOF structure. Different zirconium salts, hafnium salts and noble metal precursors have different catalytic properties and selectivities. By selecting specific salts and precursors, precise regulation of catalyst performance can be achieved. Precious metal precursors such as chloroplatinic acid, chloroiridic acid and sodium chloropalladate can be in situ reduced to generate precious metal nanoparticles during the reaction and evenly embedded into the MOF structure. This in situ confinement method not only simplifies the preparation process, but also helps to improve the utilization rate of precious metals and the stability of the catalyst.

[0019] Further, another inventive point of the present invention is that the monobasic organic acid is any one of formic acid, glacial acetic acid and propionic acid; the volume ratio of the monobasic organic acid to the N, N-dimethylformamide and ethanol mixed solvent in step S1 is (3-8): (20-50); the concentration of the 2-aminoterephthalic acid is the same as the molar concentration of the metal salt solution. The addition of the monobasic organic acid is used to adjust the pH value of the reaction system. In the synthesis process of MOF, the pH value is a key parameter, which affects the coordination reaction rate between the ligand and the metal ion and the structure of the product. By selecting a suitable monobasic organic acid and its dosage, the pH value of the reaction system can be accurately controlled, thereby optimizing the crystal structure and performance of MOF. In addition, the carboxyl group in the monobasic organic acid can coordinate with the metal ion, which helps the dispersion and stability of the metal ion in the solution, thereby promoting the coordination reaction. In addition, the organic acid can also be used as a template or structure-directing agent to guide the growth of MOF crystals to form a MOF material with a specific structure and performance. By controlling the concentration of 2-aminoterephthalic acid to be the same as that of the metal salt solution, the molar ratio between the ligand and the metal ion can be ensured to be close to the ideal value, which is conducive to the formation of a MOF material with a complete structure and excellent performance. The addition of monobasic organic acids and the precise control of the amount of ligands can help optimize the properties of MOF materials such as pore size, specific surface area and catalytic activity. The improvement of these properties helps to enhance the catalytic effect of the catalyst on specific reactions, increase the reaction rate and conversion rate, and reduce the formation of by-products. By optimizing the structure and properties of MOF materials, the stability and service life of the catalyst can also be improved. A stable catalyst structure helps to reduce the deactivation and degradation of the catalyst during the reaction, thereby maintaining long-term catalytic activity.

[0020] Furthermore, another inventive point of the present invention is that in step S2, the temperature of the stirring reaction is 120-140°C and the time is 5-12h. At a higher temperature, the molecular motion is intensified, and the collision frequency between the metal ions and the ligands (such as 2-aminoterephthalic acid) increases, thereby promoting the coordination reaction between them. This coordination reaction is a key step in forming the MOF structure, so increasing the temperature helps to accelerate the reaction rate and shorten the reaction time. The appropriate temperature range helps to form a MOF material with a regular crystal structure and good performance. Too high a temperature causes the crystal structure to be destroyed or an unstable phase to be formed, while too low a temperature makes the reaction rate too slow and cannot form a complete crystal structure. Therefore, the temperature range of 120-140°C is a relatively optimized choice. In addition, the noble metal precursor is reduced to metal nanoparticles and embedded in the MOF structure during the reaction. The temperature is crucial. High temperature helps to promote the reduction reaction and ensure the uniform distribution and stable existence of the noble metal nanoparticles in the MOF structure. The optimized MOF structure and distribution of noble metal nanoparticles can significantly improve the catalytic performance of the catalyst, which may manifest as higher catalytic activity, better selectivity and longer service life.

[0021] Further, another inventive point of the present invention is that after the stirring reaction, the product is also centrifugally washed and dried at 100-160°C for 12-20h to obtain the MOF confined precious metal material. Centrifugal washing is an effective method for removing unreacted raw materials, solvents, by-products and other impurities in the product. These impurities will affect the purity and performance of the MOF material, so the quality of the product can be significantly improved by washing. During the washing process, the crystal structure of MOF can be further stabilized, and factors that may destroy or affect the stability of MOF can be removed. At the same time, washing also helps to remove excess ligands or solvent molecules adsorbed on the surface of MOF, making the pores of MOF more unobstructed, which is conducive to subsequent applications. During the drying process, the residual solvent molecules in the product can be completely removed by high-temperature treatment. If these solvent molecules remain in MOF, they may affect its stability and catalytic performance. Therefore, drying is an important step in preparing high-quality MOF materials. Appropriate drying temperature and time help to enhance the thermal stability and chemical stability of MOF materials. High-temperature treatment can promote further solidification of the MOF crystal structure, making it more stable, which is of great significance for the long-term use and storage of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 XRD spectra of Pt@Zr-MOF prepared in Example 1 and Pt@ZH-MOF prepared in Example 2 of the present invention.

[0024] Figure 2 This is a SEM image of Pt@Zr-MOF prepared in Example 1 of the present invention; Figure 3 HADDF-STEM of Pt@Zr-MOF prepared in Example 1 of the present invention; Figure 4 The ESR detection superoxide radical generation diagram of the Pt@Zr-MOF prepared in Example 1 of the present invention and the Pt@ZH-MOF prepared in Example 2; Figure 5 Room temperature catalytic formaldehyde removal performance of Pt@Zr-MOF prepared in Example 1 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation; Figure 6 The room temperature catalytic formaldehyde removal performance of Pt@ZH-MOF-3 prepared in Example 3 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation; Figure 7 The room temperature catalytic formaldehyde removal performance of Ir@ZH-MOF prepared in Example 4 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation; Figure 8 The room temperature catalytic formaldehyde removal performance of Pd@ZH-MOF prepared in Example 5 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation; Fig. 9 The room temperature catalytic formaldehyde removal performance of Pt@Hf-MOF prepared in Example 6 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation; Fig.10 The room temperature catalytic formaldehyde removal performance of Ir@Zr-MOF prepared in Example 7 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0030] The present invention provides a method for preparing a MOF confined noble metal room-temperature composite material, comprising the following steps: (1) dispersing a metal zirconium salt and / or hafnium salt in a mixed solvent of N,N-dimethylformamide (DMF) and ethanol in a volume ratio of 1:(5-1) to prepare a metal salt solution with a concentration of 0.04-0.1 mol / L; wherein the ratio of the zirconium salt and / or hafnium salt to the mixed solvent of N,N-dimethylformamide and ethanol is (0.5-1.6) g:50 mL; The zirconium salt is any one of zirconium tetrachloride, zirconium nitrate and zirconium oxynitrate; the hafnium salt is hafnium tetrachloride or hafnium oxynitrate; the noble metal precursor is any one of chloroplatinic acid, chloroiridic acid and sodium chloropalladate; When the zirconium salt and the hafnium salt are dispersed in a mixed solvent of N,N-dimethylformamide and ethanol, the molar ratio of the zirconium salt and the hafnium salt is (0.8-0.2):(0.2-0.8), and in a preferred embodiment, the molar ratio of the zirconium salt and the hafnium salt is 0.8:0.2, 0.6:0.4, 0.4:0.6, 0.2:0.8. In a preferred embodiment, the volume ratio of DMF to ethanol is 1:5, 1:4, 1:3, 1:2, 1:1.

[0031] (2) dispersing the noble metal precursor powder in ethanol to prepare a noble metal precursor solution with a concentration of 0.12-0.48 mg / mL; The noble metal precursor is any one of chloroplatinic acid, chloroiridic acid and sodium chloropalladate.

[0032] (3) The metal salt solution and the noble metal solution are mixed evenly, wherein the mass ratio of the metal salt to the noble metal precursor is (0.5-1.6) g:(3-12) mg, and then a monobasic organic acid and a 2-aminoterephthalic acid ligand are added, and the reaction is stirred at a temperature of 120-140°C for 5-12 hours. After the reaction is completed, centrifugation is performed, the precipitate is washed with ethanol, and vacuum dried at 100-160°C for 12-20 hours to obtain a MOF confined noble metal material. The volume ratio of the monobasic organic acid to the N,N-dimethylformamide and ethanol mixed solvent in step S1 is (3-8):(20-50), so that the MOF forms defects and the noble metal nanoparticles are generated in situ, that is, the MOF crystal generation rate and the noble metal particle size are synchronously regulated.

[0033] The monobasic organic acid is any one of formic acid, glacial acetic acid and propionic acid; the concentration of the 2-aminoterephthalic acid is the same as the molar concentration of the metal salt solution.

[0034] The present invention aims at the deficiencies of the existing MOF-based formaldehyde removal catalyst preparation technology, and provides a MOF-based catalyst for efficient formaldehyde adsorption-catalytic conversion. The present invention adopts a zirconium-based and / or hafnium-based MOF confined noble metal catalyst prepared by a one-step oil bath method, and constructs a defective MOF by adjusting the volume, reaction time and temperature of a monobasic organic acid, and utilizing the competitive coordination between a monobasic organic acid and 2-aminoterephthalic acid; at the same time, the noble metal nanoparticles generated by reduction of an organic acid or DMF are confined in situ, and the MOF crystal generation rate and the noble metal particle size are synchronously regulated. Compared with the traditional method of preparing zirconium-based or hafnium-based MOF by hydrothermal reaction, the oil bath method has mild preparation conditions, simple and safe process, reduces the amount of organic solvent DMF, and is easy to mass produce. The zirconium-based and / or hafnium-based MOF confined noble metal catalyst prepared by the present invention can quickly convert formaldehyde and oxygen gas molecules adsorbed by MOF into carbon dioxide and water after activation on the surface of the noble metal nanoparticles. It has the advantages of small catalyst dosage and stable and lasting catalytic performance. That is, the present invention adopts a one-step oil bath method to react zirconium ions or hafnium ions with 2-aminoterephthalic acid to generate zirconium-based or hafnium-based MOF, and at the same time, a noble metal precursor solution is added during the in-situ self-assembly process of MOF, and the MOF crystal generation rate and the particle size of the noble metal are synchronously controlled by adjusting the volume, reaction time and temperature of the monobasic organic acid. The particle size of the noble metal in the final synthesized product is 2-3nm, and a noble metal nanoparticle catalyst with a specific particle size confined in MOF is prepared. If the volume of the monobasic organic acid is too large (small), the defects formed in MOF are too many or too large (too few or too small), and the particle size of the noble metal nanoparticles is too large (small), resulting in poor catalytic performance; the reaction time and temperature affect the formation of MOF defects and the formation rate of confined noble metal nanoparticles. High (low) reaction time and temperature usually lead to a faster (slower) reaction rate, and the particle size of the noble metal nanoparticles is too large (small), resulting in poor catalytic performance. The catalyst of the invention has mild reaction conditions for preparing the catalyst, simple process, high yield, and can be recycled. It is suitable for catalytically purifying formaldehyde pollutants in the air at room temperature and has broad application prospects.

[0035] In the present invention, the formaldehyde catalytic performance of the catalyst is evaluated by a fixed bed mobile phase test system. Test conditions: catalyst amount 0.1g, formaldehyde concentration 100ppm, mass space velocity 60,000mL⋅h -1 ⋅g cat -1 , relative humidity is 30%, temperature is 20±2℃.

[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0037] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0038] Example 1 A method for preparing a MOF confined noble metal composite material comprises the following steps: (1) Disperse 0.5 g of zirconium tetrachloride in a mixed solution of 10 mL of DMF and 40 mL of ethanol and stir until completely dissolved to prepare a 0.04 mol / L zirconium tetrachloride solution; (2) Disperse 3 mg of chloroplatinic acid in 25 mL of ethanol and stir evenly to prepare a 0.12 mg / mL chloroplatinic acid precursor solution; (3) Mix the zirconium tetrachloride solution and the chloroplatinic acid precursor solution evenly, wherein the mass ratio of the metal salt to the noble metal precursor is 0.5g:3mg, add 3 mL of glacial acetic acid and 0.04 mol / L of 2-aminoterephthalic acid ligand, stir until a clear solution is obtained, place in an oil bath at 120°C and stir for 5 h. After the reaction, centrifuge, wash the precipitate with ethanol three times and dry in a vacuum oven at 100°C for 16 h. Finally, a zirconium-based MOF-confined Pt nanocatalyst was obtained, and the sample was labeled as Pt@Zr-MOF.

[0039] Example 2 A method for preparing a MOF confined noble metal composite material comprises the following steps: (1) Dispersing 0.35 g of zirconium tetrachloride and 0.12 g of hafnium tetrachloride in a mixed solution of 15 mL of DMF and 35 mL of ethanol, stirring until completely dissolved, to prepare a mixed solution of zirconium tetrachloride and hafnium tetrachloride, wherein the concentration of zirconium tetrachloride is 0.03 mol / L and the concentration of hafnium tetrachloride is 0.01 mol / L; (2) Disperse 5 mg of chloroplatinic acid in 25 mL of ethanol and stir evenly to prepare a 0.20 mg / mL chloroplatinic acid precursor solution; (3) The zirconium tetrachloride solution and the chloroplatinic acid precursor were mixed evenly, wherein the mass ratio of the metal salt to the noble metal precursor was 0.5 g:5 mg, 6 mL of glacial acetic acid and 0.04 mol / L of 2-aminoterephthalic acid ligand were added, stirred until a clear solution was obtained, and placed in an oil bath at 140 °C for stirring and reaction for 8 h. After the reaction was completed, the solution was centrifuged, the precipitate was washed with ethanol three times, and dried in a vacuum oven at 120 °C for 20 h. Finally, a zirconium / hafnium-based MOF confined Pt nanocatalyst was obtained, and the sample was labeled as Pt@ZH-MOF. Under room temperature conditions, when the initial concentration of formaldehyde was 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate of the Pt@ZH-MOF prepared in this example were 97.7% and 96.3%, respectively.

[0040] Figure 1 The XRD spectra of Pt@Zr-MOF prepared in Example 1 of the present invention and Pt@ZH-MOF prepared in Example 2 show that the XRD diffraction peaks of Pt@Zr-MOF and Pt@ZH-MOF are similar to the UiO-66-NH2 standard spectrum, and the diffraction peak intensity is relatively high, indicating that the catalyst is highly crystalline. No diffraction peak of Pt nanoparticles is detected, proving that the Pt particles are highly dispersed on Zr-MOF or ZH-MOF.

[0041] Figure 2~3 The SEM and high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images of the Pt@Zr-MOF prepared in Example 1 of the present invention show that the Pt@Zr-MOF exhibits an octahedral morphology, Pt is highly dispersed on the Zr-MOF carrier, and the particle size of Pt is 2-3 nm. The sample structures obtained in the other embodiments are similar to those in this embodiment.

[0042] Figure 4 The ESR detection superoxide radical generation diagram of Pt@Zr-MOF prepared in Example 1 of the present invention and Pt@ZH-MOF prepared in Example 2 shows that the ESR spectra of Pt@Zr-MOF and Pt@ZH-MOF show six characteristic peaks of DMPO / superoxide radicals, indicating that O2 can be activated to generate superoxide radicals on the surface of Pt@Zr-MOF and Pt@ZH-MOF. Among them, DMPO is 5,5-dimethyl-1-pyrroline N-oxide, which is a commonly used free radical scavenger.

[0043] Figure 5The room temperature catalytic formaldehyde removal performance of the Pt@Zr-MOF prepared in Example 1 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. It can be seen from the figure that under room temperature conditions, when the initial formaldehyde concentration of the Pt@Zr-MOF prepared in Example 1 of the present invention is 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate are 98.7% and 98.3%, respectively.

[0044] Example 3 A method for preparing a MOF confined noble metal room temperature composite material comprises the following steps: (1) dispersing 0.38 g of zirconium tetrachloride and 0.1 g of hafnium tetrachloride in a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 1:5, wherein the total volume of the mixed solvent of N,N-dimethylformamide and ethanol is 50 mL, to prepare a metal salt solution with a concentration of 0.04 mol / L; the molar ratio of the zirconium salt to the hafnium salt is 0.8:0.2; (2) Disperse 3 mg of chloroplatinic acid powder in 25 ml of ethanol to prepare a chloroplatinic acid solution with a concentration of 0.12 mg / mL; (3) The metal salt solution and the chloroplatinic acid solution are mixed evenly, wherein the mass ratio of the metal salt to the precious metal precursor is 0.5g:5mg, formic acid and 0.04mol / L 2-aminoterephthalic acid ligand are added, and the mixture is stirred and reacted at a temperature of 120°C for 12h. After the reaction is completed, the mixture is centrifuged, the precipitate is washed with ethanol, and vacuum dried at 100°C for 20h to obtain a MOF confined precious metal material, which is represented as Pt@ZH-MOF-3. The ratio of the formic acid to the N,N-dimethylformamide and ethanol mixed solvent in the step (1) is 3:50. In the Pt@ZH-MOF prepared in this embodiment, the average particle size of Pt is 2.2nm.

[0045] Figure 6 The room temperature catalytic formaldehyde removal performance of Pt@ZH-MOF-3 prepared in Example 3 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. It can be seen from the figure that under room temperature conditions, when the initial formaldehyde concentration of Pt@ZH-MOF-3 prepared in Example 3 of the present invention is 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate are 90.3% and 89.9%, respectively.

[0046] Example 4 A method for preparing a MOF confined noble metal room temperature composite material comprises the following steps: (1) dispersing 0.17 g of zirconium nitrate and 0.59 g of hafnium oxynitrate in a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 1:4, the total volume of the mixed solvent of N,N-dimethylformamide and ethanol being 50 mL, to prepare a metal salt solution with a concentration of 0.05 mol / L; the molar ratio of the zirconium salt to the hafnium salt being 0.2:0.8; (2) Dispersing 12 mg of chloroiridic acid powder in 25 ml of ethanol to prepare a chloroiridic acid solution with a concentration of 0.48 mg / mL; (3) The metal salt solution and the chloroiridic acid solution are mixed evenly, wherein the mass ratio of the metal salt to the precious metal precursor is 0.8g:12mg, glacial acetic acid and 0.05mol / L 2-aminoterephthalic acid ligand are added, and the reaction is stirred at a temperature of 140°C for 5h. After the reaction is completed, centrifugation is performed, the precipitate is washed with ethanol, and vacuum dried at 160°C for 12h to obtain a MOF confined precious metal material, represented as Ir@ZH-MOF. The ratio of the monobasic organic acid to the N,N-dimethylformamide and ethanol mixed solvent in step (1) is 8:50. In the Ir@ZH-MOF prepared in this embodiment, the average particle size of Ir is 2.5nm.

[0047] Figure 7 The room temperature catalytic formaldehyde removal performance of Ir@ZH-MOF prepared in Example 4 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. It can be seen from the figure that under room temperature conditions, when the initial formaldehyde concentration of Ir@ZH-MOF prepared in Example 4 of the present invention is 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate are 93.3% and 93.1%, respectively.

[0048] Example 5 A method for preparing a MOF confined noble metal room temperature composite material comprises the following steps: (1) 0.62 g of zirconium oxynitrate and 0.4 g of hafnium oxynitrate were dispersed in a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 1:3, the total volume of the mixed solvent of N,N-dimethylformamide and ethanol being 50 mL, to prepare a metal salt solution with a concentration of 0.07 mol / L; the molar ratio of the zirconium salt to the hafnium salt being 0.6:0.4, (2) Dispersing 7.5 mg of sodium chloropalladate powder in 25 ml of ethanol to prepare a sodium chloropalladate solution with a concentration of 0.3 mg / mL; (3) The metal salt solution and the sodium chloropalladate solution are mixed evenly, wherein the mass ratio of the metal salt to the precious metal precursor is 1.0g:8.5mg, propionic acid and 0.07mol / L 2-aminoterephthalic acid ligand are added, and the reaction is stirred at a temperature of 130°C for 8h. After the reaction is completed, centrifugation is performed, the precipitate is washed with ethanol, and vacuum dried at 140°C for 18h to obtain a MOF confined precious metal material, represented as Pd@ZH-MOF. The ratio of the propionic acid to the N,N-dimethylformamide and ethanol mixed solvent in the step (1) is 5:50. In the Pd@ZH-MOF prepared in this embodiment, the average particle size of Pd is 3nm.

[0049] Figure 8 The room temperature catalytic formaldehyde removal performance of Pd@ZH-MOF prepared in Example 5 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. It can be seen from the figure that under room temperature conditions, when the initial formaldehyde concentration of Pd@ZH-MOF prepared in Example 5 of the present invention is 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate are 94.5% and 91.9%, respectively.

[0050] Example 6 A method for preparing a MOF confined noble metal room temperature composite material comprises the following steps: (1) Dispersing 1.32 g of hafnium tetrachloride in a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 1:2, the total volume of the mixed solvent of N,N-dimethylformamide and ethanol being 50 mL, to prepare a metal salt solution with a concentration of 0.08 mol / L; (2) Disperse 11.25 mg of chloroplatinic acid powder in 25 ml of ethanol to prepare a chloroplatinic acid solution with a concentration of 0.45 mg / mL; (3) The metal salt solution and the chloroplatinic acid solution are mixed evenly, wherein the mass ratio of the metal salt to the precious metal precursor is 1.3g:11.3mg, formic acid and 0.08mol / L of 2-aminoterephthalic acid ligand are added, and the reaction is stirred at a temperature of 130°C for 10 hours. After the reaction is completed, centrifugation is performed, the precipitate is washed with ethanol, and vacuum dried at 150°C for 14 hours to obtain a MOF confined precious metal material, represented as Pt@Hf-MOF. The ratio of the formic acid to the N,N-dimethylformamide and ethanol mixed solvent in the step (1) is 7:50. In the Pt@Hf-MOF prepared in this embodiment, the average particle size of Pt is 3nm.

[0051] Fig. 9The room temperature catalytic formaldehyde removal performance of Pt@Hf-MOF prepared in Example 6 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. It can be seen from the figure that under room temperature conditions, when the initial formaldehyde concentration of Pt@Hf-MOF prepared in Example 6 of the present invention is 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate are 96.4% and 96.1%, respectively.

[0052] Example 7 A method for preparing a MOF confined noble metal room temperature composite material comprises the following steps: (1) dispersing 1.6 g of zirconium nitrate in a mixed solvent of N,N-dimethylformamide and ethanol in a volume ratio of 1:1, the total volume of the mixed solvent of N,N-dimethylformamide and ethanol being 50 mL, to prepare a metal salt solution with a concentration of 0.1 mol / L; (2) dispersing 8.75 mg of chloroiridic acid powder in 25 ml of ethanol to prepare a chloroiridic acid solution with a concentration of 0.35 mg / mL; (3) The metal salt solution and the chloroiridic acid solution are mixed evenly, wherein the mass ratio of the metal salt to the precious metal precursor is 1.6g:8.8mg, propionic acid and 0.1mol / L 2-aminoterephthalic acid ligand are added, and the reaction is stirred at a temperature of 125°C for 11 hours. After the reaction is completed, centrifugation is performed, the precipitate is washed with ethanol, and vacuum dried at 110°C for 19 hours to obtain a MOF confined precious metal material, represented as Ir@Zr-MOF. The ratio of the propionic acid to the mixed solvent of N,N-dimethylformamide and ethanol in step S1 is 4:50. In the Ir@Zr-MOF prepared in this embodiment, the average particle size of Ir is 2.6nm.

[0053] Fig.10 The room temperature catalytic formaldehyde removal performance of Ir@Zr-MOF prepared in Example 7 of the present invention, wherein (A) is the formaldehyde removal rate, and (B) is the carbon dioxide generation. It can be seen from the figure that under room temperature conditions, when the initial formaldehyde concentration of Ir@Zr-MOF prepared in Example 7 of the present invention is 100 ppm, the formaldehyde removal rate and formaldehyde conversion rate are 97.5% and 96.2%, respectively.

[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a MOF confined noble metal composite material, characterized in that: The following steps are involved: S1: Dispersing zirconium salt and / or hafnium salt in a mixed solvent of N,N-dimethylformamide and ethanol to obtain a metal salt solution; the ratio of the zirconium salt and / or hafnium salt to the mixed solvent of N,N-dimethylformamide and ethanol is (0.5-1.6) g:50 mL; dispersing a noble metal precursor powder in ethanol to obtain a noble metal precursor solution; S2: Evenly mix the metal salt solution and the noble metal precursor solution, wherein the mass ratio of the metal salt to the noble metal precursor is (0.5-1.6) g:(3-12) mg, and then add a monobasic organic acid and 2-aminoterephthalic acid, and after stirring the reaction, obtain a MOF confined noble metal material.

2. The method for preparing a MOF confined noble metal composite material according to claim 1, characterized in that: In the mixed solvent of N,N-dimethylformamide and ethanol, the volume ratio of N,N-dimethylformamide to ethanol is 1:(5~1); the zirconium salt is any one of zirconium tetrachloride, zirconium nitrate and zirconium oxynitrate; the hafnium salt is hafnium tetrachloride or hafnium oxynitrate; and the concentration of the metal salt solution is 0.04~0.1 mol / L.

3. The method for preparing a MOF confined noble metal composite material according to claim 1, characterized in that: The noble metal precursor is any one of chloroplatinic acid, chloroiridic acid and sodium chloropalladate; the concentration of the noble metal precursor solution is 0.12-0.48 mg / mL.

4. The method for preparing a MOF confined noble metal composite material according to claim 1, characterized in that: When the zirconium salt and the hafnium salt are dispersed in a mixed solvent of N,N-dimethylformamide and ethanol, the molar ratio of the zirconium salt to the hafnium salt is (0.8-0.2):(0.2-0.8).

5. The method for preparing a MOF confined noble metal composite material according to claim 1, characterized in that: The monobasic organic acid is any one of formic acid, glacial acetic acid and propionic acid, and the volume ratio of the monobasic organic acid to the N,N-dimethylformamide and ethanol mixed solvent in step S1 is (3-8):(20-50); the concentration of the 2-aminoterephthalic acid is the same as the molar concentration of the metal salt solution.

6. The method for preparing a MOF confined noble metal composite material according to claim 1, characterized in that: In step S2, the stirring reaction is carried out at a temperature of 120-140° C. and a time of 5-12 h.

7. The method for preparing a MOF confined noble metal composite material according to claim 1, characterized in that: In step S2, after stirring the reaction, the product is centrifugally washed and dried at 100-160° C. for 12-20 hours to obtain the MOF confined precious metal material.

8. A MOF confined precious metal composite material, characterized in that: It is prepared by the method described in any one of claims 1 to 7; the particle size of the precious metal in the composite material is 2 to 3 nm.

9. Application of the MOF confined precious metal composite material described in claim 8 in the field of formaldehyde purification.

Citation Information

Patent Citations

  • A MOF-shaped adsorbent with formaldehyde removal function and its preparation method

    CN107694525B

  • A zirconium-based MOF catalyst with dual active sites, its preparation method and application

    CN111054443B

  • Catalyst for converting TMBQ (2,3,5-trimethyl-p-benzoquinone) into TMHQ (2,3,5-trimethylhydroquinone) and preparation method of catalyst

    CN107684921A

  • Preparation method of air purification photocatalyst with extra-small precious metal loaded on titanium dioxide surface

    CN107930620A

  • Pt NPs@MOFs photocatalyst and preparation method and application thereof

    CN108620132A